(3eLehYI CMGOjK fHhjIs ((3YHO GdhgGH Hf SdjeGf Hf YHO GdhgGH GdghT s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg KHJ HESfGO eJUd Edi QShd Gddg Udi Gddg Ydjg hSde Cf HYV CUMGH TcG Edjg GdabQ hGdbdI abGd dg Udi Gddg Ydjg hSde (B( (3Oe Ydi GdWgGQI jhSY Ydjc GdQRb s
(3BNQgG (B:s
(3SCdJ Gddg HCQRGb ebSheI hBLGd eVQhHI dGjYLd efgG TF bHd eMdg hdGjDNQ TF efgG HYO eMdg adh SCdJ Gddg Cf jLjQc ef YPGH GdbHQ hYPGH ai GdfGQ Gddge CLQfG ef YPGH GdbHQ hYPGH GdfGQ s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs